Universities as Knowledge Producers in Colombia (2018)
This book presents a report on research carried out by universities in the period 1970-2015. The general objective is to examine the link between research and the mission of universities, which are located in a context of globalization that conditions the present and future of their scientific search. The arguments discussed in each of the above mentioned sections are based on official information provided by the State as well as by national and international organizations closely related to research and higher education, and on studies and research produced by analysts of the particular field of research or university development.